Safety of hospital discharge before return of bowel function after elective colorectal surgery. Issue 5 (24th January 2020) - ,
Abstract : Background: Ileus is common after colorectal surgery and is associated with an increased risk of postoperative complications. Identifying features of normal bowel recovery and the appropriateness for hospital discharge is challenging. This study explored the safety of hospital discharge before the return of bowel function. Methods: A prospective, multicentre cohort study was undertaken across an international collaborative network. Adult patients undergoing elective colorectal resection between January and April 2018 were included. The main outcome of interest was readmission to hospital within 30â€‰days of surgery. The impact of discharge timing according to the return of bowel function was explored using multivariable regression analysis. Other outcomes were postoperative complications within 30â€‰days of surgery, measured using the Clavienâ€"Dindo classification system. Results: A total of 3288 patients were included in the analysis, of whom 301 (9Â·2 per cent) were discharged before the return of bowel function. The median duration of hospital stay for patients discharged before and after return of bowel function was 5 (i.q.r. 4â€"7) and 7 (6â€"8) days respectively ( P <â€‰0Â·001). There were no significant differences in rates of readmission between these groups (6Â·6 versus 8Â·0 per cent; P â€‰=â€‰0Â·499), and this remained the case after multivariable adjustment for baseline differences (odds ratio 0Â·90, 95 per cent c.i. 0Â·55 to 1Â·46; P â€‰=â€‰0Â·659). Rates of postoperative complications were also similar in those discharged before versus after return of bowel function (minor: 34Â·7 versus 39Â·5 per cent; major 3Â·3 versus 3Â·4 per cent; P â€‰=â€‰0Â·110). Conclusion: Discharge before return of bowel function after elective colorectal surgery appears to be safe in appropriately selected patients. Abstract : This study explored the safety of hospital discharge before return of bowel function. The study was performed across an international setting by a traineeâ€ and studentâ€led collaborative group. Discharge before return of bowel function after elective colorectal surgery appeared to be safe in appropriately selected patients. No need to wait Abstract : Antecedentes: El Ãleo es frecuente tras la cirugÃa colorrectal y se asocia con un aumento del riesgo de las complicaciones postoperatorias. Identificar las caracterÃsticas de una recuperaciÃ³n normal del trÃ¡nsito y la idoneidad para el alta hospitalaria es una tarea difÃcil. Este estudio examinÃ³ la seguridad del alta hospitalaria antes del restablecimiento de la funciÃ³n intestinal. MÃ©todos: Se llevÃ³ a cabo un estudio de cohortes prospectivo y multicÃ©ntrico a travÃ©s de una red de colaboraciÃ³n internacional. Se incluyeron pacientes adultos sometidos a resecciÃ³n electiva colorrectal entre enero y abril 2018. El objetivo principal fue el reingreso hospitalario durante los 30 primeros dÃas tras la intervenciÃ³n. Se utilizÃ³ un anÃ¡lisis de regresiÃ³n multivariable para evaluar el impacto del momento del alta en funciÃ³n del restablecimiento de la funciÃ³n intestinal. El objetivo secundario fue las complicaciones postoperatorias en los primeros 30 dÃas despuÃ©s de la cirugÃa, valoradas mediante el sistema de clasificaciÃ³n de Clavienâ€Dindo. Resultados: Se incluyeron en el anÃ¡lisis 3.288 pacientes, de los cuales 301 (9, 2%) fueron dados de alta antes del restablecimiento de la funciÃ³n intestinal. La mediana de la estancia hospitalaria de los pacientes dados de alta antes y despuÃ©s del restablecimiento de la funciÃ³n intestinal fue 5 (rango intercuartÃlico: 4â€7) y 7 (6â€8) dÃas, respectivamente ( P <â€‰0, 001). No hubo diferencias significativas en las tasas de reingreso entre estos grupos (6, 6% versus 8, 0%; P =â€‰0, 499), y este resultado se mantuvo en el anÃ¡lisis multivariable tras el ajuste por diferencias basales (razÃ³n de opotunidades, odds ratio, OR 0, 90; i.c. del 95% 0, 55â€1, 46, P =â€‰0, 659). Las tasas de complicaciones postoperarorias fueron similares en aquellos dados de alta antes o despuÃ©s del restablecimiento de la funciÃ³n intestinal (complicaciones menores: 34, 7% versus 39, 5%; complicaciones mayores 3, 3% versus 3, 4%; P =â€‰0, 110). ConclusiÃ³n: Dar de alta antes del restablecimiento de la funciÃ³n intestinal tras cirugÃa colorrectal electiva parece ser seguro en pacientes debidamente seleccionados.